Assessing the microstructure, mechanical properties, and deformation mechanism of high-strength low-alloy steel prepared via powder metallurgy - Haoyu Geng; Xiangyu Sun; Yajun Zhao; Xingjie Yin; Zhiming Du (Journal of Materials Research and Technology)
Overcoming the strength‒ductility trade-off of high-strength low-alloy steel (HSLA steel) while improving the performance of the component materials is a major challenge. In this study, we used the powder metallurgy process to prepare HSLA steel to overcome this inherent problem. The effects of the sintering temperature on the mechanical properties and microstructure were systematically investigated. HSLA steel consisting of ferrite, pearlite and bainite was sintered at different temperatures. As the sintering temperature increased, the ferrite and pearlite contents decreased, whereas the bainite content increased. The tensile strength increased, whereas the elongation decreased. When the sintering temperature was 1250 °C, the ultimate strength of the HSLA steel reached 1087.5 ± 17.2 MPa, and the elongation exceeded 12.83% ± 0.46%. During the austenite transformation process, alloy elements form carbides, which alternate with ferrite to form pearlite. During plastic deformation, ferrite/pearlite formed substructures and deformed to adapt to coordinated deformation, whereas the twinning generated within bainite provided sufficient strength. Microcracks were generated at the interface between the soft and hard phases or within the hard phase.